2013
DOI: 10.1128/jvi.02026-12
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral DNA Methylation and Epigenetic Repression Are Mediated by the Antiviral Host Protein Daxx

Abstract: Integrated retroviral DNA is subject to epigenetic transcriptional silencing at different frequencies. This process is mediated by repressive DNA methylation and histone modifications on viral chromatin. However, the detailed mechanisms by which retroviral silencing is initiated and maintained are not well understood. Using a model system in which avian sarcoma virus (ASV) DNA is epigenetically repressed in mammalian cells, we previously found that a cellular scaffolding protein, Daxx, acts as an antiretrovira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 73 publications
2
53
0
Order By: Relevance
“…2A) (87). In addition, Daxx also recruits Dmnt1 to the viral DNA, resulting in long terminal repeat (LTR) methylation and transcriptional repression (88). These findings suggest that Daxx/HDAC/Dmnt1 complexes play a role in initiating epigenetic silencing, possibly as part of an antiviral response against retroviruses (87,89).…”
Section: Daxx Impairment By Virion Proteins: a Role In Latency And Simentioning
confidence: 83%
“…2A) (87). In addition, Daxx also recruits Dmnt1 to the viral DNA, resulting in long terminal repeat (LTR) methylation and transcriptional repression (88). These findings suggest that Daxx/HDAC/Dmnt1 complexes play a role in initiating epigenetic silencing, possibly as part of an antiviral response against retroviruses (87,89).…”
Section: Daxx Impairment By Virion Proteins: a Role In Latency And Simentioning
confidence: 83%
“…Many studies have shown that cell death-modulating protein DAXX functions as a transcriptional repressor [1-4]. DAXX associates with RelB, a transcription factor of the NF-κB family that directly controls the expression of numerous apoptosis- and autophagy-relevant genes, including tumor suppressor protein kinases DAPK1/3 [1;2].…”
Section: Introductionmentioning
confidence: 99%
“…In mouse embryo fibroblasts (MEFs) [2], as well as in the PCa cell lines [unpublished data], DAXX represses expression of these genes via mechanisms that include its binding to DNA methyl transferases (DNMTases) and hypermethylation of the promoter regions of the corresponding genes [2]. DAXX also recruits DNMTases to viral DNA so as to initiate its epigenetic repression [4]. A number of publications have reproducibly shown that DAXX interacts directly with DNMTs and employs DNA methylation as a major mechanism of repression [2-4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, both studies indicate an unconventional mobility of PML-NBs, which appear to sense viral nucleoprotein complexes or replication intermediates, resulting in movement of the respective proteins even to the cytoplasm. Additionally, PML and hDaxx were implicated as contributing to the control of retroviral latency via epigenetic repression (12,13).…”
Section: Pml-nbs and Intrinsic Immunitymentioning
confidence: 99%